Intracellular Angiotensin-II Measurement in Streptozotocin-Induced Rat Vascular Smooth Muscle Cells and Its Relationship with Angiotensin-II Receptors - Çiçek, Zehra; Akıllıoğlu, Kübra; Yaşar, Zehra Gül; Doğan, Ayşe (The European Research Journal, 2026)
Objectives: Angiotensin II (Ang-II) is vital constituent of renin angiotensin aldosterone system and increases in some cardiovascular diseases such as diabetes. However, there are not enough studies related to intracellular and extracellular Ang-II levels and its interaction with Ang-II type 1 and 2 receptors (ATR1, ATR2) in vascular smooth muscle cells (VSMCs). We aimed to investigate healthy and diabetic rat model of VSMCs (H-VSMCs, D-VSMCs) proliferation and Ang-II levels. Methods: VSMCs were isolated from the aorta of healthy and diabetic Wistar rats. Diabetic model was achieved by intravenous administration of 45 mg/kg streptozotocin. Firstly, different Ang-II (0-1000 μM) concentration was performed for dose study. Ang-II (0.1 μM), Ang-II type 1 receptor (ATR1) antagonist (Olmesartan, 1 μM) and Ang-II type 2 receptor (ATR2) antagonist (PD123,319, 1 μM) were practiced together, and thereafter cell proliferation was evaluated by MTT (3-(4,5-Dimethylthiazol-2-yl)-2,5-Diphenyltetrazolium Bromide) method. Intracellular and extracellular Ang-II levels were measured by ELISA kit. Results: While H-VSMCs proliferation increased in Ang-II 0.1, 0.01, 0.001 and 0.0001 μM, D-VSMCs proliferation increased Ang-II 0.1 and 0.01 μM applications (P<0.05). Olmesartan 1 µM inhibited proliferation in H-VSMCs. Ang-II detected intracellular and extracellular groups of VSMCs, but no significant difference was found between H-VSMCs and D-VSMCs groups (P˃0.05). Conclusions: Ang-II enhances proliferation of H-VSMCs and D-VSMCs. There is no relationship that could be established between intracellular and extracellular Ang-II levels, H-VSMCs and D-VSMCs proliferation and Ang-II receptors.